Screening of Immunostimulatory Activity from Indonesian Kampung (Gallus domesticus) Egg White Water Extract: in vitro study - Mulyani, Rizka; Harmayani, Eni; Nurliyani; Ishida, Momoko; Nishi, Kosuke; Sugahara, Takuya (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2021)
The most popular Indonesian native chicken, known as kampung chicken, is maintained under free-range conditions therefore it is prone to high environmental stress. Indonesian native chicken and its product are always regarded as having health benefits compared to commercial chicken by Indonesian society. But there is still limited report regarding Indonesian native chicken and its product. This study focused on screening immunostimulatory activity from Indonesian native chicken egg white using in vitro approaches as a functional food. Indonesian native chicken egg white (NEW) was extracted using distilled water supplemented to human-human hybridoma HB4C5 cells to examine the IgM production stimulating activity using ELISA. The gene expression was also examined using qRT-PCR. The ability of NEW on stimulating immunoglobulin production by mouse splenocytes was analyzed. Commercial egg white water extract (CEW) was used as a comparison. The data were analyzed using One-way ANOVA and continued by using post-hoc analysis using Tukey’s multiple comparison test. The results showed that NEW and CEW modulated IgM production by the HB4C5 cells 8.72-fold and 6.75-fold, respectively, compared to control. NEW stimulated immunoglobulin (Ig) production by the mouse splenocytes higher than CEW. To conclude, NEW provides an immunostimulating activity that can potentially act as a health-promoting food.